Sosialisasi Penanaman Karakter Dan Literasi Melalui Jurnal Siswa (Pelita Jiwa) Pada Siswa Kelas 6 Sd Negeri Neglasari - Apriandi, Firman; Riska, Muhammad (Jurusan Teknik Informatika dan Komputer, 2025)
Character Building and Literacy through Student Journals (PELITA JIWA) is an innovative effort designed to instill character and literacy values ​​in grade 6 students of Neglasari State Elementary School. The background of this program is the challenges in the digital era, where students are more often exposed to technology such as games and social media, so they lack responsibility, empathy, and interest in reading. This program uses the Student Journal Book as a habituation tool to record obligatory worship activities, character, literacy, and daily reflection. The implementation of the program involves several strategic steps, such as determining habituation behavior, socializing plans to parents, providing exemplary examples, and evaluating periodically. Collaboration between teachers, students, and parents is an important aspect in this program showing a significant increase in student behavior during the four months of implementation. Data recorded an increase in the percentage of students who routinely perform obligatory prayers from 79% to 96.6%, book reading activities increased, and habits of maintaining cleanliness such as washing dishes and making beds also experienced a positive trend. In addition, this program increases cooperation between parents and teachers, as well as student awareness of the importance of literacy. PELITA JIWA is effective in forming positive habits in students through structured habituation and exemplary principles. Sustainable strategies are able to change habits into ingrained habits (habituation). With this approach, it can be used as a reference for good practices to support character education and literacy in other schools.